Toxic di Media Sosial dalam Perspektif Hadis dengan Metode Tematik - Mirta Aprilia Iuliatno; Salim Rosyadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
In today's digital era, social media has developed into a major platform for networking, sharing information and communicating. Toxic is behavior on social media that is described as destructive, hostile, and embarrassing. Conflict, societal divisions, and psychological harm can all result from this practice. This study uses a thematic method with a thematic approach. The results of this study discuss from the perspective of hadith which refers to the sayings and deeds of the Prophet Muhammad, there are guidelines and standards that can help individuals deal with harmful social media. This journal will look at the negative effects of social media from a hadith point of view, emphasizing the meaning and application of hadiths. In the results of his research, it is hoped that people will become more aware of the harmful effects of toxic social media and take steps to reduce destructive behavior and promote inclusive and healthy communication by taking into account the principles and teachings of the Prophet Muhammad.